Governing California - Giventer, Lawrence L. (McGraw-Hill, 2004)
This brief, affordable text examines the essential elements of California governance and answers fundamental questions: What do you and I, as ordinary residents, citizens, and taxpayers of California, need to know about our government? How does government work and how does it affect us? Governing California presents a new way to perceive the student of California government: as a participant.